From King to People: Jayabaya's Prophecy and Its Evolution in Javanese Political Culture - Wijaya, Tomy; Alauwiyah, Fatimah; Kurohman, M Taofik (Faculty of Humanities, Andalas University, Padang, West Sumatra in cooperation with Kato Institute., 2025)
This research examines the changing role of Jayabaya’s Prophecy in Javanese political culture, tracing its development from the kingdom era to the present. Initially, the prophecy served as a tool for legitimising elite authority. Over time, however, it evolved into a symbol of resistance, especially in the aftermath of the 1998 Reform movement. The study applies historical methods heuristics, verification, interpretation, and historiography drawing on various sources such as prophetic manuscripts, cultural artefacts, digital media, and popular narratives. Narrative, semiotic, and discourse analysis are used to explore the symbolic meanings of concepts like zaman edan (“age of madness”) and Ratu Adil (“Just Ruler”). The findings reveal that interpretations of the prophecy are fluid and context-dependent. Under the New Order regime, it was employed as an ideological instrument to strengthen state power. In contrast, during the Reform era, the prophecy was reappropriated by society as a cultural counter-narrative against state authority. In contemporary discourse, it is increasingly interpreted as a post-apocalyptic vision reflecting both ongoing crises and aspirations for justice and equality. This study highlights the enduring political relevance of myths and cultural heritage. They function not only as instruments of legitimisation but also as powerful means of resistance and collective imagination, offering insight into the intersection of mythology, power, and identity in Indonesian cultural politics.